Analisis Pengaruh Rasio NPL, LDR, CAR, BOPO, dan NIM terhadap Profitabilitas Bank: Studi pada Bank Umum Konvensional yang Terdaftar di BEI Tahun 2020-2024 - Aisya Indah Oktaviani; Wisnu Mawardi (Diponegoro Journal of Management, 2025)
The research aims to examine the effect of the independent variables Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), Operational Expenses and Operational Income (BOPO), Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) on bank profitability. Bank profitability is measured by Return on Assets (ROA) as the dependent variable. The research uses secondary data on a population of 47 banks listed on the Indonesia Stock Exchange for the period 2020-2024. 26 banks were selected using purposive sampling. By using a multiple linear regression analysis model and the Generalised Least Squares (GLS) method to analyse the research. The results of this research indicate that NPL and BOPO have a significant negative effect on ROA. LDR and NIM have a significant positive effect on ROA. CAR has an insignificant negative effect on ROA.